The Effect of Dexmedetomidine on Outcomes of Cardiac Surgery in Elderly Patients. Issue 2 (April 2017) - Cheng, H.; Li, Z.; Young, N.; Boyd, D.; Atkins, Z.; Ji, F.; Liu, H.
Abstract : (Abstracted from J Cardiothorac Vasc Anesth, 30(6):1502–1508, 2016) The purpose of this retrospective investigation was to study the effects of the perioperative use of dexmedetomidine (Dex) on outcomes in elderly patients undergoing cardiac surgery. Dexmedetomidine, a highly selective α2 -adrenergic agonist, controls the activity of the sympathetic nervous system by binding to the α2 -receptors present in both the central and peripheral nervous systems and inhibiting the release of norepinephrine, thus modulating sympathetic activity.